Validation of Vanillylmandelic Acid (VMA) with Plasma Metanephrine and Normetanephrine for Screening Adrenal Medullary Disorders - Khalid, Usama Bin; Haroon, Zujaja Hina; Aamir, Muhammad; Ashraf, Sana; Bibi, Afshan; Javaid, Haroon (Pakistan Armed Forces Medical Journal, 2023)
Objective: To validate urinary Vanillylmandelic acid (VMA) for screening adrenal medullary disorders, taking plasma-free Metanephrine as the gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology,Rawalpindi, in collaboration with Armed Forces Institute of Urology, Rawalpindi from Pakistan, Jan 2020 to Mar 2021. Methodology: One hundred and thirty (130) symptomatic hypertensive patients with adrenal masses on ultrasound were selected Urine and blood samples were collected under specified conditions after taking necessary precautions and subsequently analyzed. Taking plasma Metanephrine as a reference, sensitivity, specificity and predictive values were calculated at predefined cut-off values. Results: In a young population with a mean age of 28.55±5.54 years, headache, palpitations and sweating were the predominant symptoms having a frequency of 130(100%), 116(89.2%) and 111(85.4%), respectively. Twenty-four hours urinary Vanillylmandelic acid had lower sensitivity (66.3%) than a random urinary VMA/cr ratio (72.1%) but similar specificity(97.7%). On the other hand, plasma-free Normetanephrine had 100% sensitivity but lower specificity (93.2%). ROC curve was plotted, and AUC for 24 hours urinary VMA, urinary VMA/cr ratio and plasma-free Normetanephrine were 0.820, 0.849 and0.966, respectively. Conclusion: Plasma-free Metanephrine could be used for screening pheochromocytoma and other adrenal medullary disorders like paraganglionoma. In addition, VMA/cr ratio can be used for biochemical confirmation of the disease owing to the high specificity found in our study.